Evaluation of the WATCHMAN left atrial appendage closure device. (November 2014) - Alli, Oluseun; Holmes, David
Abstract : Left atrial appendage device occlusion for the preventions of systemic thromboembolism and stroke represents a major breakthrough in the field of cardiovascular disease. The wide prevalence of atrial fibrillation with devastating consequences of thromboembolic stroke as a result of thrombus arising from the left atrial appendage has led to the development of transcatheter and surgical based occlusion devices. Though this device is yet to be formally approved for a clinical indication in the USA, the WATCHMAN appendage occlusion device remains the most rigorously examined and studied of all transcatheter-based devices in this space. This review will focus on the needs assessment in this space, the technology of the current WATCHMAN device, trials and studies looking at safety and efficacy, specific patient populations who might benefit as well as future perspectives.